A Celebration of Life! An African American Ethnic Academy & BioPharmaceutical Technology Center Institute Science Outreach Partnership - Bielec, Barbara (Proceedings of the Wisconsin Space Conference, 2011)
The primary goal of â€œA Celebration of Lifeâ€ is to support the continued development of African American and other studentsâ€™ interest in science, and to assist in providing them with the tools for success in school. A long-term goal is to increase the number of minority students who successfully complete high school science courses and who choose to pursue STEM careers. In partnership with the African American Ethnic Academy, Inc. (AAEA), a Madison non-profit organization, the BioPharmaceutical Technology Center Institute (BTC Institute) offered "A Celebration of Life XVI: Healthy Bodies on Earth and in Space!" during summer 2011. Two week sessions for elementary and middle school students were held weekday mornings at the BioPharmaceutical Technology Center, in Madison, Wisconsin. These programs represent a 16- year collaboration between AAEA and the BTC Institute that prioritizes offering a rich range of hands-on science activities for students.Â